2014
DOI: 10.9738/intsurg-d-13-00069.1
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Esophageal Squamous Cell Carcinoma With Intramural Gastric Metastasis Invading Liver and Pancreas: A Case Report

Abstract: A 59-year-old Japanese man was admitted to our hospital because of a 1-month history of dysphagia. Endoscopic examination revealed a superficial esophageal squamous cell carcinoma and a giant gastric tumor. Computed tomography showed that the gastric tumor was directly invading the liver and pancreas. Because of the risk of the gastric tumor causing obstruction and bleeding, we performed a subtotal esophagectomy, proximal gastrectomy, left lateral segmentectomy of liver, and pancreatosplenectomy with gastric t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The incidence of IGM is higher in advanced-stage ESCC[ 5 , 22 ], as only a few cases of IGM in the early-stage ESCC have been reported. From mucosal ESCC, to our best knowledge, only 6 cases (including the present one) have been documented[ 10 - 13 , 23 ]. Therefore, although the probability of lymphatic metastasis is very low, it can still occur even if the tumor is confined to the mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of IGM is higher in advanced-stage ESCC[ 5 , 22 ], as only a few cases of IGM in the early-stage ESCC have been reported. From mucosal ESCC, to our best knowledge, only 6 cases (including the present one) have been documented[ 10 - 13 , 23 ]. Therefore, although the probability of lymphatic metastasis is very low, it can still occur even if the tumor is confined to the mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, what really surprised us was that from November 2021 (PET-CT suggested abnormal cardiac metabolism) to November 2022 (gastroendoscopy revealed a Borrmann type II lesion in the cardiac area), metastases to the cardia grew rapidly and were so large that no significant primary lesions were found in the esophagus. The cardiac area is rich in blood supply, which is conducive to the root proliferation of squamous cells, and the cardiac area is significantly large[ 23 , 24 ]. Primary gastric adenocarcinoma sometimes has a similar gross appearance but a higher incidence in the lower part of the stomach.…”
Section: Discussionmentioning
confidence: 99%
“…However, Kato et al reported no marked difference in outcomes between chemotherapy and chemoradiation for patients with gastric IM [ 11 ]. It is generally agreed that gastric IM requires multidisciplinary treatment, including surgery [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Findings regarding gastrointestinal cancers are summarized in Table 2. [57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72]…”
Section: Gastrointestinal Cancermentioning
confidence: 99%